Brain-derived neurotrophic factor gene polymorphism rs6265 and elite athlete status in four independent populations - Anikevičiūtė, Gabija; Urnikytė, Alina; Massidda, Myosotis; Calò, Carla Maria; Tocco, Filippo; Takaragawa, Mizuki; Miyamoto-Mikami, Eri; Murakami, Haruka; Miyachi, Motohiko; Fuku, Noriyuki; Humińska-Lisowska, Kinga; Łosińska, Kinga; et al. (Biology of Sport, 2025)
This research aimed to investigate the association of the BDNF rs6265 polymorphism with elite athletic status in four different populations: Japanese and European Caucasian cohorts from Italy, Poland, and Lithuania. A total of 1,644 professional athletes (868 Japanese, 177 Italian, 369 Polish, 230 Lithuanian) and 1,948 non-athlete controls (healthy, unrelated 821 Japanese, 102 Italian, 371 Polish, and 654 Lithuanian individuals) were genotyped. The athletes were stratified into endurance-oriented, sprint/power-oriented, and team sports groups. Statistical analysis was performed using R version 4.2.0. The results showed that the allele/genotype distribution of BDNF rs6265 was significantly different between the athlete and control groups and varied across all analysed populations. The minor A allele was significantly more common in the Japanese compared to Europeans, and the G allele/GG genotype was significantly more prevalent in Polish and Lithuanian individuals compared to Italians. European athletes were less likely to have the rare AA genotype than sedentary controls. The GG genotype was more prevalent among Italian athletes, particularly those in team sports, who were about twice as likely to have the GG genotype compared to controls. Lithuanian athletes were more likely to have the GA genotype compared to controls. This was especially true for Lithuanian sprint/power athletes, who had a twofold greater probability of having the GA genotype compared to controls. The BDNF rs6265 variant indicates genetic differences across the four populations (ancestry-relevant heterogeneity) and highlights its potential influence on elite athletic status for the Italian (GG genotype) and Lithuanian (GA genotype) populations.